2018
DOI: 10.1007/s00213-018-5076-4
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of instrumental (operant) learning: interference, varieties of context, and mechanisms of contextual control

Abstract: This article reviews recent research on the extinction of instrumental (or operant) conditioning from the perspective that it is an example of a general retroactive interference process. Previous discussions of interference have focused primarily on findings from Pavlovian conditioning. The present review shows that extinction in instrumental learning has much in common with other examples of retroactive interference in instrumental learning (e.g., omission learning, punishment, second-outcome learning, discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 128 publications
14
90
1
Order By: Relevance
“…However, there has been considerably less attention to evaluating the prevalence and extent of relapse following the end of treatment. The stronger impact of omission on reinstatement and reacquisition is consistent with the view that reinforcers delivered during omission training may provide an important part of the "context" that controls behavioral inhibition (e.g., Bouton, 2019;Bouton & Schepers, 2014;Trask, Schepers, & Bouton, 2015;Uhl & Garcia, 1969). For example, studies have found less spontaneous recovery (Davidson & Walker, 1970;Topping & Ford, 1974;Zeiler, 1971), reinstatement (Harman, 1973;Topping & Larmi, 1973;Uhl, 1973;Uhl & Garcia, 1969;Uhl & Sherman, 1971), and slower reacquisition (Mulick, Leitenberg, & Rawson, 1976;Pacitti & Smith, 1977;Uhl & Garcia, 1969;Uhl & Sherman, 1971) following omission training when compared to extinction.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…However, there has been considerably less attention to evaluating the prevalence and extent of relapse following the end of treatment. The stronger impact of omission on reinstatement and reacquisition is consistent with the view that reinforcers delivered during omission training may provide an important part of the "context" that controls behavioral inhibition (e.g., Bouton, 2019;Bouton & Schepers, 2014;Trask, Schepers, & Bouton, 2015;Uhl & Garcia, 1969). For example, studies have found less spontaneous recovery (Davidson & Walker, 1970;Topping & Ford, 1974;Zeiler, 1971), reinstatement (Harman, 1973;Topping & Larmi, 1973;Uhl, 1973;Uhl & Garcia, 1969;Uhl & Sherman, 1971), and slower reacquisition (Mulick, Leitenberg, & Rawson, 1976;Pacitti & Smith, 1977;Uhl & Garcia, 1969;Uhl & Sherman, 1971) following omission training when compared to extinction.…”
supporting
confidence: 76%
“…For example, studies have found less spontaneous recovery (Davidson & Walker, 1970;Topping & Ford, 1974;Zeiler, 1971), reinstatement (Harman, 1973;Topping & Larmi, 1973;Uhl, 1973;Uhl & Garcia, 1969;Uhl & Sherman, 1971), and slower reacquisition (Mulick, Leitenberg, & Rawson, 1976;Pacitti & Smith, 1977;Uhl & Garcia, 1969;Uhl & Sherman, 1971) following omission training when compared to extinction. The stronger impact of omission on reinstatement and reacquisition is consistent with the view that reinforcers delivered during omission training may provide an important part of the "context" that controls behavioral inhibition (e.g., Bouton, 2019;Bouton & Schepers, 2014;Trask, Schepers, & Bouton, 2015;Uhl & Garcia, 1969). The stronger impact on spontaneous recovery, however, may be consistent with the possibility that omission creates a more durable form of behavioral suppression.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…One of the most powerful sources of behavioral change is extinction learning, which allows individuals to withhold instrumental actions when their consequences change. Rather than erasing such actions from one's repertoire, current views propose that extinction generates new inhibitory learning that, when incorporated into previously acquired behavior, acts selectively to reduce instrumental performance (1).…”
Section: Introductionmentioning
confidence: 99%